2022
DOI: 10.1002/aqc.3850
|View full text |Cite
|
Sign up to set email alerts
|

A riverine biodiversity hotspot in northern Myanmar supports three new and narrowly endemic freshwater mussel species

Abstract: 1. The Western Indochina Subregion (Myanmar) represents a freshwater biodiversity hotspot of worldwide significance and houses a plethora of endemic freshwater species, among which are amphibians, fish, and various aquatic invertebrates.2. The freshwater mussel (Bivalvia: Unionidae) fauna of western Indochina is characterized by high taxonomic richness, with almost all species and several genera being endemic to the subregion. Furthermore, there are a number of species endemic to a single basin or even to a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Recently it has been shown that multiple freshwater taxa penetrated river systems of Northeastern Europe using the Volga River as a migration corridor [45]. Considering the complex hydrological periglacial network during the LGM [46,47] and reconstructed A. anatina distribution during the Late Quarternary [8], we can speculate that multiple connections between rivers across Europe also occurred. Extremely low genetic differentiation between groups of populations within panEUR lineage indicates high gene flow and supports our suggestion about migration flows across the species range.…”
Section: Discussionmentioning
confidence: 88%
“…Recently it has been shown that multiple freshwater taxa penetrated river systems of Northeastern Europe using the Volga River as a migration corridor [45]. Considering the complex hydrological periglacial network during the LGM [46,47] and reconstructed A. anatina distribution during the Late Quarternary [8], we can speculate that multiple connections between rivers across Europe also occurred. Extremely low genetic differentiation between groups of populations within panEUR lineage indicates high gene flow and supports our suggestion about migration flows across the species range.…”
Section: Discussionmentioning
confidence: 88%
“…Modern homogenization of freshwater faunas is a global phenomenon, of course (Rahel, 2002), but invasions of freshwater mussels beyond their native ranges are usually supported by more or less comparable environmental conditions (Bolotov et al, 2016; Kondakov et al, 2020). Hence, the establishment of non‐native populations of temperate species in tropical water systems (or vice versa) is hardly expected, although a few exceptions may occur (Bolotov, Konopleva, et al, 2022; Vikhrev et al, 2017). Moreover, we argue that at least one taxonomic expert should check freshwater mussel‐focused manuscripts received by non‐taxonomic journals to avoid possible misidentification of target species.…”
Section: Discussionmentioning
confidence: 99%
“…Many species of freshwater mussels may be distinguished based on conchological features, but there are complexes of cryptic species that do not share clear diagnostic characters and cannot be divided using the morphological characters alone. The genera Sinanodonta , Lamellidens , Lens and Yaukthwa are good examples of such taxonomically complicated clades (Bolotov et al, 2020; Bolotov, Konopleva, et al, 2022; Konopleva et al, 2019; Lopes‐Lima et al, 2020; Pfeiffer et al, 2021). The best way to identify freshwater mussel species from these groups is the DNA‐based approach supplemented with morphological data and biogeographical evidence (Konopleva et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, some cryptic species may face endangerment or extinction before they are discovered (Cheng et al, 2024). Nowadays, many researchers recognize the significance of cryptic species for biodiversity conservation and acknowledge that these species may be more susceptible to threats in the current complex environment (Bolotov et al, 2024;Nair et al, 2012;Niemiller et al, 2013;Sano et al, 2022). Our research is focused on an understudied group of Nodularia in order to unveil further insights into this taxon.…”
Section: Conservation Implicationsmentioning
confidence: 99%